2023
DOI: 10.1002/smtd.202201252
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Activity of the Oxidation Stabilized Ti3C2Tx MXene in Decomposing Methylene Blue, Bromocresol Green and Commercial Textile Dye

Abstract: Two‐dimensional MXenes are excellent photocatalysts. However, their low oxidation stability makes controlling photocatalytic processes challenging. For the first time, this work elucidates the influence of the oxidation stabilization of model 2D Ti3C2Tx MXene on its optical and photocatalytic properties. The delaminated MXene is synthesized via two well‐established approaches: hydrofluoric acid/tetramethylammonium hydroxide (TMAOH‐MXene) and minimum intensive layer delamination with hydrochloric acid/lithium f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 77 publications
0
13
1
Order By: Relevance
“…Therefore, we tested the self-cleaning ability of the films under UV or white light irradiation using discoloration of a model cationic dye, rhodamine B (RhB). The negative zeta potential of the flakes with functional groups (−F and −O terminations) on the surface helps MXene effectively adsorb cationic dyes, such as RhB. , Additionally, we also tested the RhB adsorption on the bare rGO thin-film surface. In contrast to the MXene-based thin film, we found that bare rGO showed a poor interaction with RhB (Figure S21).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we tested the self-cleaning ability of the films under UV or white light irradiation using discoloration of a model cationic dye, rhodamine B (RhB). The negative zeta potential of the flakes with functional groups (−F and −O terminations) on the surface helps MXene effectively adsorb cationic dyes, such as RhB. , Additionally, we also tested the RhB adsorption on the bare rGO thin-film surface. In contrast to the MXene-based thin film, we found that bare rGO showed a poor interaction with RhB (Figure S21).…”
Section: Resultsmentioning
confidence: 99%
“…MXene has a high electron migration rate due to the presence of titanium atoms in its structure, which can serve as an electron acceptor to facilitate the transport of photogenerated carriers and prohibit their complexation. 36 In addition, the switchable wettability of the PMPP membranes shows significant potential for continuous separation and in situ photodegradation of heavy oil/water/ light oil ternary mixtures. The well-controlled separation process is shown in Figure 5a and Video S2.…”
Section: One-step Dye Removal and Oil/water Separation Based On Syner...mentioning
confidence: 99%
“…It is also easy to integrate photothermal materials with the PNIPAm hydrogel to create photothermally stimulated responsive composite hydrogels . As an emerging two-dimensional material with a significant variety of end groups (such as −O, −OH, and −F), MXene has attracted much interest in the fields of oil/water separation and photodegradation due to its excellent light absorption characteristics and exceptional charge separation efficiency for photodegradation . By mixing MXene with PNIPAm, PNIPAm can achieve photothermally responsive behavior by utilizing the outstanding photothermal properties of MXene.…”
Section: Introductionmentioning
confidence: 99%
“…[ 9–12 ] These fascinating materials can boost the generation and utilization of charge carriers, the most active in pollutant decomposition. [ 13–15 ] Their activity is confined to their ultrathin nature, which concentrates quantum effects in the planar dimension. [ 16,17 ]…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] These fascinating materials can boost the generation and utilization of charge carriers, the most active in pollutant decomposition. [13][14][15] Their activity is confined to their ultrathin nature, which concentrates quantum effects in the planar dimension. [16,17] An excellent example of such 2D materials is the MXene family, named early transition metal carbides and nitrides.…”
Section: Introductionmentioning
confidence: 99%